2018
DOI: 10.1292/jvms.18-0241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Vibrio parahaemolyticus</i> in seafood and water environment in the Mekong Delta, Vietnam

Abstract: A total of 449 samples including 385 seafood and 64 water samples in the Mekong Delta of Vietnam collected in 2015 and 2016 were examined. Of 385 seafood samples, 332 (86.2%) samples were contaminated with Vibrio parahaemolyticus and 25 (6.5%) samples were pathogenic V. parahaemolyticus carrying tdh and/or trh genes. The tdh gene positive V. parahaemolyticus strains were detected in 22 (5.7%) samples and trh gene positive V. parahaemolyticus strains were found in 5 (1.3%) samples. Of 25 pathogenic V. parahaemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…V. parahaemolyticus is recognized as a cosmopolitan bacterium frequently isolated from the USA, Canada (Newton et al 2012;Taylor et al 2018), Asia (Letchumanan Chan & Lee 2014;Yang et al 2017), European countries (Cantet et al 2013;Passalacqua et al 2016), South America (Martinez-Urtaza 2013; Raszl et al 2016) and Africa (Malainine et al 2013). Some V. parahaemolyticus strains are pathogenic to humans and were responsible for 25% of seafood-borne diseases (Martinez-Urtaza et al 2013;Tran et al 2018). This virulence was associated especially with the production of thermostable direct haemolysin (tdh) and/or thermostable-related haemolysin (trh) (Wang et al 2018), also known as the Kanagawa phenomenon (KP) (Leoni et al 2016).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…V. parahaemolyticus is recognized as a cosmopolitan bacterium frequently isolated from the USA, Canada (Newton et al 2012;Taylor et al 2018), Asia (Letchumanan Chan & Lee 2014;Yang et al 2017), European countries (Cantet et al 2013;Passalacqua et al 2016), South America (Martinez-Urtaza 2013; Raszl et al 2016) and Africa (Malainine et al 2013). Some V. parahaemolyticus strains are pathogenic to humans and were responsible for 25% of seafood-borne diseases (Martinez-Urtaza et al 2013;Tran et al 2018). This virulence was associated especially with the production of thermostable direct haemolysin (tdh) and/or thermostable-related haemolysin (trh) (Wang et al 2018), also known as the Kanagawa phenomenon (KP) (Leoni et al 2016).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…These results are consistent with the findings of Jones et al (2012) who obtained tdh-negative and trh-positive isolates of Vibrio species from Canada, Maine, and Washington during the early summer, indicating a potential preferential distribution of these strains in northern areas. A study carried out by Tran et al (2018) (Raghunath, 2015). This was also reflected in a previous report that trh-positive V. parahaemolyticus strains constitute a higher proportion of the total V. parahaemolyticus population in the Mid-Atlantic region than in other areas during the summer (DePaola et al, 2010).…”
Section: Resultsmentioning
confidence: 59%
“…These results are consistent with the findings of Jones et al (2012) who obtained tdh -negative and trh -positive isolates of Vibrio species from Canada, Maine, and Washington during the early summer, indicating a potential preferential distribution of these strains in northern areas. A study carried out by Tran et al (2018) on 385 sea food samples demonstrated the presence of tdh and trh positive V. parahaemolyticus strains in 25 samples. Out of theses 25 samples, only 2 samples have V. parahaemolyticus strains with both tdh and trh gene and rest 23 samples have V. parahaemolyticus strains either with tdh and trh virulence gene.…”
Section: Resultsmentioning
confidence: 99%
“…Odeyemi [ 7 ] reported a meta-analysis of the incidence of V. parahaemolyticus from 2003 to 2015, which showed that the prevalence of V. parahaemolyticus was 52.9% for clam and 48.3% for shrimp. Besides, other studies also prove the fact that V. parahaemolyticus prevalence is relatively more in shellfish [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 85%